Validity of self-reported Peripheral Neuropathy (PN) as a surrogate marker for clinically-determined PN in HIV/AIDS patients initiating ART in Masaka, Uganda 2004-2008 - Pitso, Mpho Nomthimkhulu (My University, 2022)
Background Globally, the prevalence of HIV/AIDS is about 37.9 million with Sub-Saharan Africa being the epicenter of the pandemic with 25.6 million people living with HIV/AIDS as of June 2019 (1). While opportunistic HIV-related infections have declined steadily in recent years, peripheral sensory neuropathies related to HIV and ART continue to be high and recurrent (2). Peripheral neuropathy (PN) is a neurological disorder regularly found in People Living with HIV (PLHIV), individuals with dysproteinemic disorders, and those on chemotherapy (3,4). Brief Peripheral Neuropathy Screen (BPNS), a screening tool used for symptom reporting and clinical assessment of PN, is not widely used in resource-limited settings due to cost constraints (3). For resource-limited settings, it would be beneficial to have a surrogate marker for determining PN in PLHIV. A surrogate marker is a physical measurement that can be used as a substitute or be considered a valid predictor of the true recognized outcome measure (clinical assessment) (5). For validation of a surrogate marker, Ross Prentice came up with two conditions; if both of these are satisfied then the surrogate can be considered to be valid (6). The Prentice criteria firstly indicate that a surrogate marker needs to be correlated with the true endpoint and secondly it should capture the entire effect of treatment upon the true endpoint (6).
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Epidemiology to the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2022